Involvement of tumor immune microenvironment metabolic reprogramming in colorectal cancer progression, immune escape, and response to immunotherapy - Nicolini, Andrea; Ferrari, Paola (Frontiers in Immunology, 2024)
Metabolic reprogramming is a key hallmark of tumors, developed in response to hypoxia and nutrient deficiency during tumor progression. In both cancer and immune cells, there is a metabolic shift from oxidative phosphorylation (OXPHOS) to aerobic glycolysis, also known as the Warburg effect, which then leads to lactate acidification, increased lipid synthesis, and glutaminolysis. This reprogramming facilitates tumor immune evasion and, within the tumor microenvironment (TME), cancer and immune cells collaborate to create a suppressive tumor immune microenvironment (TIME). The growing interest in the metabolic reprogramming of the TME, particularly its significance in colorectal cancer—one of the most prevalent cancers—has prompted us to explore this topic. Colorectal cancer (CRC) exhibits abnormal glycolysis, glutaminolysis, and increased lipid synthesis. Acidosis in CRC cells hampers the activity of anti-tumor immune cells and inhibits the phagocytosis of tumor-associated macrophages (TAMs), while nutrient deficiency promotes the development of regulatory T cells (Tregs) and M2-like macrophages. In CRC cells, activation of G-protein coupled receptor 81 (GPR81) signaling leads to overexpression of programmed death-ligand 1 (PD-L1) and reduces the antigen presentation capability of dendritic cells. Moreover, the genetic and epigenetic cell phenotype, along with the microbiota, significantly influence CRC metabolic reprogramming. Activating RAS mutations and overexpression of epidermal growth factor receptor (EGFR) occur in approximately 50% and 80% of patients, respectively, stimulating glycolysis and increasing levels of hypoxia-inducible factor 1 alpha (HIF1α) and MYC proteins. Certain bacteria produce short-chain fatty acids (SCFAs), which activate CD8+ cells and genes involved in antigen processing and presentation, while other mechanisms support pro-tumor activities. The use of immune checkpoint inhibitors (ICIs) in selected CRC patients has shown promise, and the combination of these with drugs that inhibit aerobic glycolysis is currently being intensively researched to enhance the efficacy of immunotherapy.